H∞ Analysis of Linear Systems with Jumps: Applications to Sampled-Data Control*. Issue 30 (2016) - Souza, Matheus; Fioravanti, André R.; Gonçalves, Alim P.C.
Abstract: This note focuses on H ∞ analysis of a certain class of hybrid linear systems. The main results presented in this paper are embedded in the context of Riccati equations and convex optimisation. These results, together with the classic Small-Gain Theorem, can be applied to design state feedback controllers for sampled-data systems subject to time-delays.